Deciphering the O-Glycosylation of HKU1 Spike Protein With the Dual-Functional Hydrophilic Interaction Chromatography Materials - Cui, Yun; Dong, Xuefang; Zhang, Xiaofei; Chen, Cheng; Fu, Dongmei; Li, Xiuling; Liang, Xinmiao (Frontiers in Chemistry, 2021)
HKU1 is a human beta coronavirus and infects host cells via highly glycosylated spike protein (S). The N-glycosylation of HKU1 S has been reported. However, little is known about its O-glycosylation, which hinders the in-depth understanding of its biological functions. Herein, a comprehensive study of O-glycosylation of HKU1 S was carried out based on dual-functional histidine-bonded silica materials (HBS). The enrichment method for O-glycopeptides with HBS was developed and validated using standard proteins. The application of the developed method to HKU1 S1 subunit resulted in 46 novel O-glycosylation sites, among which 55.6% were predicted to be exposed on the outer protein surface. Moreover, the O-linked glycans and their abundance on each HKU1 S1 site were analyzed. The obtained O-glycosylation dataset will provide valuable insights into the structure of HKU1 S.